2005
DOI: 10.1680/geot.2005.55.4.297
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of plane strain tests on sands using a particulate approach

Abstract: This paper describes the results of a series of numerical plane strain test simulations on a particulate material, carried out using the three-dimensional particle flow code PFC-3D. Samples comprised about 10 000 non-spherical particles, each formed by strongly bonding two spheres together. The simulations demonstrate the ability of such a model to capture the essential macro-features of soil behaviour as observed in laboratory tests, including the dependence of peak strengths on the initial void ratio relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…The residual stages in the synthetic specimen are remarkable and consistent with each other, which in turn verifies the homogeneity of our synthetic materials and confirms that the experimental apparatus has little influence on the test data error. Previous studies also presented a noticeable residual strain range of sand specimens [33]. The residual loading capacity in our study can be explained by the stable zone formed in the center (Figure 8), which is the result of a shear-type failure.…”
Section: Mechanical and Deformation Behavior Of Synthetic Specimens Usupporting
confidence: 71%
See 3 more Smart Citations
“…The residual stages in the synthetic specimen are remarkable and consistent with each other, which in turn verifies the homogeneity of our synthetic materials and confirms that the experimental apparatus has little influence on the test data error. Previous studies also presented a noticeable residual strain range of sand specimens [33]. The residual loading capacity in our study can be explained by the stable zone formed in the center (Figure 8), which is the result of a shear-type failure.…”
Section: Mechanical and Deformation Behavior Of Synthetic Specimens Usupporting
confidence: 71%
“…Although these specimens were compressed to a residual stage, they can keep stable with the existing of this stable zone. Powrie et al [33] and Alshibli et al [34] found similar failure shapes in Ottawa sand and numerical samples, respectively. Powrie et al defined this failure pattern as 'conjugate shear bands'.…”
Section: Failure Patterns Of Synthetic Specimensmentioning
confidence: 79%
See 2 more Smart Citations
“…Herein c, fm and fcv are the angle of dilation, the mobilized friction angle and the friction angle at critical state respectively. Powrie et al (2005) reported a linear relation, which was equivalent to sin c=c(sin fmsin fcv) with c §0.5, between a measure of dilation šc dened as šc=tan -1 (dev/de1), the mobilized friction angle f and the critical state friction angle fcv. For plane strain compression, the experimental data based empirical relation fm=fcv+0.8c, which can be alternatively approximated as sin c §1.33(sin fm-sin fcv), is``operationally indistinguishable'' from Rowe's stress-dilatancy relation (Bolton, 1986).…”
Section: Introductionmentioning
confidence: 99%